Project BOOST: Effectiveness of a multihospital effort to reduce rehospitalization. Issue 8 (22nd July 2013) - Hansen, Luke O.; Greenwald, Jeffrey L.; Budnitz, Tina; Howell, Eric; Halasyamani, Lakshmi; Maynard, Greg; Vidyarthi, Arpana; Coleman, Eric A.; Williams, Mark V.
Abstract : BACKGROUND: Rehospitalization is a prominent target for healthcare quality improvement and performance‐based reimbursement. The generalizability of existing evidence on best practices is unknown. OBJECTIVE: To determine the effect of Project BOOST (Better Outcomes for Older adults through Safe Transitions) on rehospitalization rates and length of stay. DESIGN: Semicontrolled pre–post study. SETTING/PARTICIPANTS: Volunteer sample of 11 hospitals varying in geography, size, and academic affiliation. INTERVENTION: Hospitals implemented Project BOOST‐recommended tools supported by an external quality improvement physician mentor. METHODS: Pre–post changes in readmission rates and length of stay within BOOST units, and between BOOST units and site‐designated control units. RESULTS: The average rate of 30‐day rehospitalization in BOOST units was 14.7% prior to implementation and 12.7% 12 months later ( P  = 0.010), reflecting an absolute reduction of 2% and a relative reduction of 13.6%. Rehospitalization rates for matched control units were 14.0% in the preintervention period and 14.1% in the postintervention period ( P  = 0.831). The mean absolute reduction in readmission rates in BOOST units compared to control units was 2.0% ( P  = 0.054 for signed rank test comparing differences in readmission rate reduction in BOOST units compared to site‐matched control units). CONCLUSIONS: Participation in Project BOOST appeared to be associated with a decrease in readmission rates. Journal of Hospital Medicine 2013;8:421–427. © 2013 Society of Hospital Medicine